From Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) 2022 2025 - talking points related to WorldFish and IAA activities and manual - Baum, Michael; Al-Zu'bi, Maha (2023)
This workshop is an expert consultation on the current status of groundwater resources for use in integrated aquaculture-agriculture and saline landscapes in new lands. The workshop was conducted at the WorldFish facility in Abbassa, with the remote participation of the F2R-CWANA leadership team. The number of participants in the workshop reached thirty. This is the presentation given by Initiative leads Michael Baum and Maha Al-Zu'bi.